PENGELOLAAN PARKIR DI TEPI JALAN UMUM DI KOTA PADANG - Meita Lefi Kurnia dan Harifal Swandi (Normative Jurnal Ilmiah Hukum, 2017)
One of the characteristics of regional financing in implementing autonomy is the source of Local Own Revenue (PAD), which consists of the results of local taxes, the results of regional retribution and the results of the management of local wealth that is separated as a major component of APBD sources. In order to increase PAD, the Government must first know what is the source of the PAD. Potential and potential revenue source sources are Parking Levies on the Public Roads as set forth in Article 1 of Padang City Regional Regulation No. 1 of 2016 on the Second Amendment to Padang City Regulation Number 11 Year 2011 on Public Service Levies stating "Parking Levies in The Public Road is a local levy as payment for public roadside services provided by the Regional Government. From the observation while not yet well coordinated parking places beside public roads in Padang City, it seems there are still many unofficial parking officers who operate on the side of the road, therefore it needs to be studied how the management of public roads parked in the city of Padang. This research is an empirical law research or sociological law research, the data needed is primary and secondary data, while the data collection technique used is with observation and structured interviews, After the data is processed then done data analysis by using qualitative analysis that is by expressing reality in the form of a sentence, to the data obtained from the results of the study, without using the figures in the statistical formula. From the results of research and discussion can be concluded, parking providers in the city of Padang: a. The responsibility for the implementation of parking is implemented by the Department of Transportation. b. For implementing the operational technique of parking operation is carried out by the technical implementing unit of the agency, abbreviated as UPTD.c. UPTD is under and responsible to the Head of Transportation Department.